Neural Foundations of Creativity: A Systematic Review (2017)
When considering the importance of the human cognitive function of creativity, we often overlook the fact that it is due to human creativity and to the constant search for new sensory stimuli that our world has, throughout the years, been one of innovation in every aspect of our existence —in the sciences, the humanities, and the arts. Almost everything that surrounds us is the result of human creativity, therefore it is not difficult to understand that although neuroscientific research has led to valuable perceptions into the probable underpinnings of this multifaceted ability, the precise neurological substrates that underlie creativity are yet to be determined. Despite the establishment of a strong link between creativity and divergent thinking, other brain networks have been implicated in this mental process. The following review underlines recent studies on the neural foundations of creativity. A comprehensive analysis of the upmost important facts will be presented, with emphasis on concepts, tests, and methods that have been used to study creativity, and how they have outlined a pathway to the key understanding of this unique human ability. © 2016 Asociación Colombiana de Psiquiatría